Reappraising suppression: subjective and physiological correlates of experiential suppression in healthy adults - Lemaire, Mathieu; El-Hage, Wissam; Frangou, Sophia (Frontiers in Psychology, 2014)
Background: Emotion regulation strategies based on suppressing behavioural expressions of emotion have been considered maladaptive. However this may not apply to suppressing the emotional experience (experiential suppression). The aim of this study was to define the effect of experiential suppression on subjective and physiological emotional responses. Methods: Healthy adults (N=101) were characterized in terms of the temperament, personality, and hedonic capacity using the Tridimensional Personality Questionnaire, the Eysenck Personality Questionnaire, the Fawcett-Clark Pleasure Scale and the State-Trait Anxiety Inventory. Participants were shown positive, negative and neutral pictures from the International Affective Picture System under two conditions, passive viewing and experiential suppression. During both conditions, subjective ratings of the intensity and duration of emotional responses and physiological measures of skin conductance (SC) and cardiac inter-beat interval (IBI) to each picture were recorded. Results: Negative pictures elicited the most intense physiological and emotional responses regardless of experimental condition. Ratings of emotional intensity were not affected by condition. In contrast, experiential suppression, compared to passive viewing, was associated with decreased duration of the emotional response, reduced maximum SC amplitude and longer IBIs independent of age, picture valence, personality traits, hedonic capacity and anxiety. Conclusion: These findings demonstrate that experiential suppression may represent an adaptive emotion regulation mechanism associated with reduced arousal and cardiovascular activation.